Water vapor compression and its various applications. (December 2018) - Hu, Bin; Wu, Di; Wang, R.Z.
Abstract: From the view of environment protection, water refrigerant can completely satisfy the requirements of the energy-saving and emission-reduction. Currently, centrifugal, roots and screw compressor are three main kinds of water vapor compressors. Centrifugal water vapor compressor has the advantage of larger volume flow rate, but it has smaller single stage compression ratio, high discharge temperature, droplet sensitivity and severe and expensive blade materials. The largest volume flow rate and smallest compression ratio system is more suitable application field for centrifugal water vapor compressor. Roots water vapor compressor has the advantages of less vibration components and simple structure. However, it also has smaller compression ratio compared with screw water vapor compressor, which results in that it is usually used in the small volume flow rate, medium heating capacity and temperature rise systems. Screw water vapor compressor has the advantages of good stability, larger compression ratio and wet compression; however its volume flow rate is not very large. It is more suitable for the refrigeration system with medium and smaller volume flow rate and larger compression ratio. The main applications of water vapor compressors can be divided into mechanical vapor recompression (MVR) system, water vapor heat pump system and water vapor refrigeration system. MVR system is a high efficiency and energy saving technology and its advantages lie in the simple process, low operation cost, simple structure and small covered area. Water vapor refrigeration and heat pump systems both face the challenges of evaporation in vacuum, big compression ratio, small volumetric refrigeration capacity, large volume flow rate and high exhaust temperature. Nevertheless, the coefficients of performance (COP) of them are better than the traditional refrigeration and heat pump systems under certain conditions. Some typical applications of water vapor systems with their own special characteristics are also introduced. Highlights: Various kinds of water vapor compressors are reviewed and compared. Various systems with water vapor compressor are analyzed and summarized. Typical application cases are introduced and discussed. A new high temperature heat pump system with water refrigerant is proposed.